Healthy Participation, Healthy People : A Review of Social Accountability Initiatives in Indonesian Policies and Programs - Laugen, Chris; Siagian, Clara; Bennouna, Cyril; Kusumaningrum, Santi (World Bank, Washington, DC, 2019)
As social accountability (SA) initiatives in Indonesia continue to grow, evidence shows that mechanisms to engage citizens to monitor service provision and provide constructive feedback on large-scale programs in the public sector still need improvement. SA, or citizens’ ability to hold governing actors and their partners accountable for their actions and commitments, is recognized as a fundamental right and an indispensable means of strengthening national health systems. The Government of Indonesia’s commitment to improve basic service delivery to poor and vulnerable populations represents an opportunity to apply SA approaches to improve the access and quality of health services. This report aims to inform efforts to improve SA in Indonesia’s health sector, particularly maternal and child health services. It gives an overview of common approaches to building social accountability, using examples from other comparable low- and middle-income countries, to extract lessons learned. It then analyses Indonesia’s national regulatory and policy framework related to SA initiatives in the health sector. Next, it reviews Indonesian initiatives that have included SA components to identify programmatic opportunities, challenges, and remaining gaps for improving SA in Indonesia’s health sector. Finally, it provides evidence-based recommendations for future SA policy and programming initiatives in Indonesia. Three common thematic SA approaches emerged from this review. These include: building awareness among communities, creating voice, and empowering action. This report finds that SA initiatives that include all three elements through multiple mechanisms are more likely to succeed. Programs need to develop comprehensive approaches that fit local contexts, accommodate multi-sector partnerships, and account for existing power dynamics and risks associated with increased decision-making authority. Efforts to prepare service providers and local officials to solicit routine citizen feedback on services, and to work with citizens to develop solutions that work for everyone, should be mainstreamed into all health system strengthening programs.